INVENTORIES AND THE STATEMENT OF FUNDS. - Moonitz, Maurice (The Accounting Review, 1943)
This article focuses on the inventories and the statement of funds. The statement of funds is one important tool of analysis employed to trace the how of funds as a preliminary to assessing its significance. The need for a statement of funds arises from the fact that present-day accounting procedures are geared primarily to the determination of income and to the correlative movements in costs and values of assets and liabilities, not to the measurement of the now of funds. To produce an analysis of funds, consequently, a device such as the statement-of-funds work sheet is required to transform income-measuring data so as to constitute a reflection of financial circulation. If a statement of cash receipts and disbursements is available, as in budgetary procedure, with receipts classified by source and disbursements by destination, no necessity exists for preparing a statement of funds from modified balance-sheet and income-statement data, because a cash statement of this nature is itself a statement of the flow of funds.